Consumers' willingness to pay for natural food: Evidence from an artefactual field experiment - Giuseppina Migliore; Massimiliano Borrello; Alessia Lombardi; Giorgio Schifani (Agricultural and Food Economics, 2018)
Among foods with credence attributes, food with "natural" components have received in the last years particular attention by consumers. This study applies the BDM incentive compatible mechanism to explore young (18-35 years old) consumers' interest and willingness to pay for chewing gums having the natural attribute. Our analysis shows that over 68% of consumers are interested in the natural attribute and are willing to pay a price premium. We also find that consumers' higher age and interest in the environment have significant impacts on consumers' preferences for the natural attribute.
Keywords: 330; Credence attributes; Chewing gum; BDM; Willingness to pay; Information effect